Progressive failure prediction of pinned joint in quasi-isotropic laminates used in pipelines - Abd-Elhady,A.A. (2018)
Abstract To simulate the progressive failure of pinned joint in quasi-isotropic [0/45/-45/90]s glass fiber reinforced polymer (GFRP) composite laminates used in pipeline, 3-D finite element model is employed in the present work. Hashin failure criterion as a progressive damage model associated with Virtual-Crack-Closing-Technique (VCCT) delamination model has been adopted to predicate the failure due to fiber breakage, matrix cracking and delamination in composite pinned joint. This technique may be an innovation for this paper. W/D has been changed to get different modes of failure, i.e. tension, shear-out and bearing failures, in composite pinned joint,. The failure mode for GFRP composite pinned joint has been predicted finally after prediction the failure at each ply laminate of stacking sequence [0/45/-45/90]s. An experimental work of pinned joint in quasi-isotropic GFRP composite laminates has been conducted to validate the present numerical results. The numerical and experimental results showed an agreement between them. Therefore, the present 3D finite element model can be considered as a good candidate to expect the progressive damage in composite pinned joints.